The Pantun Pitutur Song: A Study of Educational Values in The Music Show of The Marawis Suma Budhaya Group - Sulaksono, Projo; Sumaryanto Florentinus, Totok; Wadiyo, Wadiyo (Universitas Negeri Semarang, 2020)
This study aims to analyze the educational values of that is implemented through the process of interaction in the musical play of the